High concentrate diet induced inflammatory response and tight junction disruption in the mammary gland of dairy cows. (March 2023) - Wang, Yan; Wang, Lairong; Meng, Meijuan; Huo, Ran; Ma, Nana; Chang, Guangjun; Shen, Xiangzhen
Abstract: This study aimed to investigate the effect and mechanism of a high concentrate (HC) diet on the inflammatory response and cellular tight junctions (TJs) in the mammary gland of dairy cows. Twelve lactating Holstein dairy cows were randomly assigned into low concentrate (LC) and HC groups (n = 6), which were fed with LC diet and HC diet respectively for 3 weeks. The HC diet lead to subacute ruminant acidosis with a rumen pH < 5.6 more than 3 h daily. The HC diet triggered an inflammatory response with increased levels of inflammatory cytokines in the lacteal vein, upregulated expression of inflammation-related genes, elevated activity of myeloperoxidase, and inflammatory cells infiltration in the mammary gland. Furthermore, the HC diet induced the activation of nuclear factor kappa B (NF-κB) and mitogen-activated protein kinase (MAPK) signaling pathways with enhanced phosphorylation ratios of NF-κB P65, inhibitor of NF-κB (IκB), P38 and extracellular signal-regulated kinase 1/2 (ERK1/2) as well as decreased ratios of DNA methylation and chromatin compaction of genes coding for proinflammatory cytokines, which contributed to the upregulation of proinflammatory cytokine expression. The HC diet also destroyed the integrity of TJ with discontinuous and decreased expression levels of zonula occludens-1, Occludin, Claudin-4 and increased expression level of Claudin-1 in the mammary epithelial cells compared with LC group. Conclusively, the HC diet induced the activation of NF-κB and MAPK signaling pathways and epigenetic modifications, promoted the transcription of proinflammatory cytokines, and finally caused inflammatory response and TJ disruption in the mammary gland of dairy cows. Highlights: High concentrate diet activated NF-κB and MAPK signaling pathway and triggered inflammatory response in mammary gland. DNA methylation and chromatin compaction contributed to high concentrate diet induced inflammatory response. High concentrate diet lead to tight junction disruption in mammary gland.